Formation of Long-Lived Color Centers for Broadband Visible Light Emission in Low-Dimensional Layered Perovskites - Booker, Edward P; Thomas, Tudor H; Quarti, Claudio; Stanton, Michael R; Dashwood, Cameron D; Gillett, Alexander J; Richter, Johannes M; Pearson, Andrew J; Davis, Nathaniel J. L. K; Sirringhaus, Henning; Price, Michael B; Greenham, Neil C; et al. (Journal of the American Chemical Society, 2017)
We investigate the origin of the broadband visible emission in layered hybrid lead-halide perovskites and its connection with structural and photophysical properties. We study ⟨001⟩ oriented thin films of hexylammonium (HA) lead iodide, (C6H16N)2PbI4, and dodecylammonium (DA) lead iodide, (C12H28N)2PbI4, by combining first-principles simulations with time-resolved photoluminescence, steady-state absorption and X-ray diffraction measurements on cooling from 300 to 4 K. Ultrafast transient absorption and photoluminescence measurements are used to track the formation and recombination of emissive states. In addition to the excitonic photoluminescence near the absorption edge, we find a red-shifted, broadband (full-width at half-maximum of about 0.4 eV), emission band below 200 K, similar to emission from ⟨110⟩ oriented bromide 2D perovskites at room temperature. The lifetime of this sub-band-gap emission exceeds that of the excitonic transition by orders of magnitude. We use X-ray diffraction measurements to study the changes in crystal lattice with temperature. We report changes in the octahedral tilt and lattice spacing in both materials, together with a phase change around 200 K in DA2PbI4. DFT simulations of the HA2PbI4 crystal structure indicate that the low-energy emission is due to interstitial iodide and related Frenkel defects. Our results demonstrate that white-light emission is not limited to ⟨110⟩ oriented bromide 2D perovskites but a general property of this class of system, and highlight the importance of defect control for the formation of low-energy emissive sites, which can provide a pathway to design tailored white-light emitters.